Reliability-based inspection optimization of complex structures: A brief retrospective - Onoufriou, Toula; Frangopol, D.M. (My University, 2002)
This paper presents a brief retrospective of the development and application of reliability-based techniques for assessment of complex structures with emphasis on inspection optimization of offshore and bridge structures. An optimal reliability-based inspection program is the key to optimize the lifetime maintenance cost while maintaining the safety and serviceability of complex structures at acceptable levels. The experience of the two authors from the two different fields, of offshore structures, first author, and highway bridges, second author, is brought together in this paper, which examines the approaches adopted in each field, and the reasons which influenced the way the methods have been developed and applied. The similarities and differences between inspection optimizations for offshore and bridge structures are also discussed.
Keywords: Reliability; Maintenance; Structural Systems Research Project